2016
DOI: 10.18632/oncotarget.8650
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer stem cells with p53 modulators

Abstract: Cancer stem cells (CSC) typically over-express aldehyde dehydrogenase (ALDH). Thus, ALDHbright tumor cells represent targets for developing novel cancer prevention/treatment interventions. Loss of p53 function is a common genetic event during cancer development wherein small molecular weight compounds (SMWC) that restore p53 function and reverse tumor growth have been identified. Here, we focused on two widely studied p53 SMWC, CP-31398 and PRIMA-1, to target ALDHbright CSC in human breast, endometrial and pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
(48 reference statements)
2
8
1
Order By: Relevance
“…The proportions of ALDH high and CD133 +ve cells in the two endometrial cancer cell lines reported here are similar to those in other studies [40,41,42]. This is the first study, however, in which the two populations of cells with cancer stem cell activity have been directly compared at a functional and genetic level.…”
Section: Discussionsupporting
confidence: 88%
“…The proportions of ALDH high and CD133 +ve cells in the two endometrial cancer cell lines reported here are similar to those in other studies [40,41,42]. This is the first study, however, in which the two populations of cells with cancer stem cell activity have been directly compared at a functional and genetic level.…”
Section: Discussionsupporting
confidence: 88%
“…The proportions of ALDH high and CD133 +ve cells in the two endometrial cancer cell lines reported here are similar to those in other studies (42)(43)(44). This is the first study, however, in which the two populations of cells with cancer stem cell activity have been directly compared at a functional and genetic level.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Zhang et al reported that CP significantly reduced cancer stem cell (CSC) content, defined as aldehyde dehydrogenase (ALDH) over-expressed cells, in human breast, endometrial, or pancreas carcinoma cell lines in vitro [ 22 ]. CSCs were identified in various tumors including MM.…”
Section: Discussionmentioning
confidence: 99%